Effect of chronic alcohol consumption on brain structure in males with alcohol use disorder without a familiar history of alcoholism. (May 2022) - Martínez-Maldonado, Andrés; Verdejo-Román, Juan; Sion, Ana; Rubio, Gabriel; Pérez-García, Miguel; Jurado-Barba, Rosa
Abstract: Structural brain damages caused by chronic alcohol consumption have been extensively reported. However, the neuroimaging findings in people with alcohol use disorder (AUD) are relatively inconsistent. This inconsistency may be due to the influence of different variables that are not always considered, such as the presence of a family history of alcoholism (FHA). The main aim of this research is to study the gray (GM) and white matter (WM) volumes in male participants with AUD without FHA compared to healthy control males (HC) without FHA. For this study, we included 19 participants with AUD without FHA and 18 HC males without FHA. T1-weighted images were acquired with a General Electric Signa Exite 1.5 T scanner. GM and WM tissues were calculated using Diffeomorphic Anatomical Registration Through Exponentiated Lie algebra (DARTEL). All analyses were controlled for age and total brain volume. The statistical threshold was calculated with AlphaSim and further adjusted to account for the non-isotropic smoothness of structural images, according to Hayasaka et al. (2004) . The obtained main results showed that, relative to the HC group, the participants with AUD without FHA had significantly lower GM in several brain structures, reflecting relatively purely the effects of chronic alcohol intake on brain volume. GM structure integrity is relevant for the efficient functioning of low and high-order cognitive processes used in everyday life, and its damage seems to be related to the severity/intensity/chronicity of the AUD. As such, it becomes relevant to assess and follow brain structural changes through the dependence course.